CONSIDERING THE INTEGRATED VALUE ENGINEERING AND RISK MANAGEMENT TECHNIQUES DURING THE DESIGN PHASE IN CONSTRUCTION PROJECTS – ITS IMPLICATIONS TO PROJECT OBJECTIVES (A Case Study on Certain Irrigation Projects, North Sulawesi Province) - Pedju, Mohamad Jamin; Mawu, Emelly (JURNAL ILMIAH MEDIA ENGINEERING, 2013)
In encouraging of the success of irrigation projects, the implementation of value engineering technique as well as managing risks as recognized and as important in management process has been placed into consideration, and put those two concurrently into a single integrated process. The integrated approach is considered to assist a clear link to achieve the project’s objectives in terms of, in this case, time, cost, and quality. The purpose of this study is to identify and analyze factors in conjunction with risks and value and in association with optimal approach on the development of construction projects via design solutions during the design and engineering phase in accordance to the project’s objectives, based on data from questionnaires, interviews, and projects’ documentations, mostly from the respondents’ responses. Those factors are ranked in term of their effects to project time, cost, and quality. Four factors that are related to project time, five factors linked to project cost, and two factors associated with project quality. Other result is factors that affecting simultaneously, as an overall to the project objectives, consists of two related with Value process and the other three were linked to Risks. Although the findings were concerned to the implementation of the integration of those two techniques, in accordance with improvement during the design phase, some possible limitations are expected to exist, for example, time consuming to the extended process. In addition, education along with training is needed to the prosperous of the integrated approach.Keywords: value engineering, risk management, integrated, construction project, design phase